6 A Novel EUS-Guided Intratumoral Delivery of Submicron Particle Paclitaxel (SPP) for the Treatment of Locally Advanced Pancreatic Cancer (LA-PAC): A Prospective Safety, Tolerability and Preliminary Efficiency Study - Lo, Simon; Hendifar, Andrew; Sharma, Neil; Othman, Mohamed; Mendoza-Ladd, Antonio; Verco, Shelagh; Verco, James; diZerega, Gere (The American journal of gastroenterology, 2019)
INTRODUCTION:PAC is an aggressive malignancy with a 5-year survival rate of < 8%. LA-PAC poses a particularly difficult therapeutic challenge. The aim of this study is to assess safety and preliminary efficacy of direct injection of submicron paclitaxel particles (SPP), which have been shown to reside at the delivery site for up to at least 100 days in a prior study, for control of PAC disease activity.METHODS:LA-PAC subjects were enrolled to receive EUS-guided intratumoral SPP delivery of 6, 10, or 15 mg/mL concentrations, ≤20% of the tumor volume, in a standard “3+3” dose-escalation protocol. The highest dose with an acceptable safety and tolerability profile, 15 mg/mL, is evaluated in the second study phase, which is ongoing, designed to enroll 12 subjects to receive two equal-dose injections 4 weeks apart. All subjects are followed for 6 months (m) to monitor their clinical parameters. Tumor responses are being assessed at 3- and 6 m post-initial injection.RESULTS:Seventeen subjects have been enrolled to date, comprising 10 subjects in the dose escalation group and 7 in the second phase. Of the 10 dose escalation subjects, seven have completed the 6 m study; one died just prior to the 6 m visit; 2 withdrew with disease progression. Of the 7 in the second phase, 5 have had both injections; 3 have completed 3m follow-up; 2 have withdrawn due to disease progression. Transient mild/moderate abdominal pain was noted in 4 subjects. Bradycardia, nausea, back pain, bloating, nausea and pancytopenia were also recorded. Acute pancreatitis has not been encountered. Plasma paclitaxel levels were detectable through days 1 and 2 at very low levels, returning to baseline in all but 1 subject by wk 4, supporting slow release of SPP from the delivery site. All but 1 subject had a very low plasma level of ≤10 ng/mL. Plasma CA19-9 was normal or stable in half of the subjects and continued to rise in half during first 3 m of treatment. In one subject the injected tumor appeared cyst-like at time of second injection, without signs of infection, and another subject in the second phase was down-staged at wk 16 and underwent surgical resection.CONCLUSION:SPP appears to be safe and tolerable when administered by intratumoral PAC injection at up to 15 mg/mL on two occasions 4-wks apart. One subject was down-staged and has undergone surgical resection. These are encouraging results and warrant further investigation of this novel treatment approach.